PERSEPSI SISWA TERHADAP LAYANAN TENAGA TATA USAHA DI UPT SMA NEGERI 1 PINRANG - Rachmah, Sitti; Ardiansyah, Muhammad; Irmawati, Irmawati (LPPM Institut Pendidikan Nusantara Global, 2023)
This study examines student perceptions of administrative staff services at UPT SMA Negeri 1 Pinrang. The purpose of this study was to describe student perceptions of administrative staff services which can be seen from the six indicators of measuring service namely; ability, attitude, appearance, attention, action and responsibility (accountability). The type of research used in this study is descriptive quantitative survey method. The research subjects were class XI students of SMA Negeri 1 Pinrang with a total sample of 81 students determined by the sampling technique names Purposive Sampling using the Slovin formula. Test the validity of the research instrument using Product Moment and test the reliability using Cronbach Alpha. Development of instruments through expert validators by supervising lecturers and entrusted lecturers. The instrument used was a questionnaire with respondents. Methods of data collection in the form of observation, questionnaires and documentation. Data analysis techniques using descriptive quantitative analysis. The results showed that students' perceptions of administrative staff services at UPT SMA Negeri 1 Pinrang seen from six indicators were as follows: (1) Ability was in the good category, the highest percentage was achieved by the statement that administrative staff provided ideas or services new. (2) The attitude is in the good category, the highest percentage is achieved by the statement that the administrative staff is able to provide excellent service. (3) Appearance, the highest percentage was achieved by honest administration staff statements in providing information. (4) Attention, the highest percentage was achieved by the statement that the administrative staff respects the opinions of others. (5) Action, the highest percentage was achieved by the statement that administrative staff can make information system services and student administration reporting. (6) Responsibility (accountability), the highest percentage is achieved by the statement that administrative staff are objective and fair in providing services to students. The results of all indicators are in the very good category.